Feeding Stonehenge: cuisine and consumption at the Late Neolithic site of Durrington Walls. (October 2015) - Craig, Oliver E.; Shillito, Lisa-Marie; Albarella, Umberto; Viner-Daniels, Sarah; Chan, Ben; Cleal, Ros; Ixer, Robert; Jay, Mandy; Marshall, Pete; Simmons, Ellen; Wright, Elizabeth; Pearson, Mike Parker
Abstract: Abstract : The discovery of Neolithic houses at Durrington Walls that are contemporary with the main construction phase of Stonehenge raised questions as to their interrelationship. Was Durrington Walls the residence of the builders of Stonehenge? Were the activities there more significant than simply domestic subsistence? Using lipid residue analysis, this paper identifies the preferential use of certain pottery types for the preparation of particular food groups and differential consumption of dairy and meat products between monumental and domestic areas of the site. Supported by the analysis of faunal remains, the results suggest seasonal feasting and perhaps organised culinary unification of a diverse community.